2005
DOI: 10.1128/iai.73.11.7304-7310.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Protection against PulmonaryYersinia pestisInfection

Abstract: Pulmonary infection with the bacterium Yersinia pestis causes pneumonic plague, an often-fatal disease for which no vaccine is presently available. Antibody-mediated humoral immunity can protect mice against pulmonary Y. pestis infection, an experimental model of pneumonic plague. Little is known about the protective efficacy of cellular immunity. We investigated the cellular immune response to Y. pestis in B-cell-deficient MT mice, which lack the capacity to generate antibody responses. To effectively prime p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(157 citation statements)
references
References 38 publications
9
148
0
Order By: Relevance
“…Several previous studies have demonstrated that IFN-γ and TNF-α contribute to protection against a lethal systemic Y. pestis challenge, and that cytokine-mediated Th1-type cellular immunity is very important to overcome the immunosuppression induced by Y. pestis infection. 7,31,48,49 In this study, we observed that the Y. pestis 201 or the EV induced not only the increase of IFN-γ and TNF-α production but also that of IL-2 secretion, revealing that the Y. pestis 201 or the EV could induce cytokine-mediated Th1-type cellular immune response in Chinese-origin rhesus macaque model. Moreover, the secretion of IL-4, IL-5, or IL-6 was significantly elevated in the immunized groups after immunization with the Y. pestis 201 or the EV.…”
Section: 84142mentioning
confidence: 77%
See 2 more Smart Citations
“…Several previous studies have demonstrated that IFN-γ and TNF-α contribute to protection against a lethal systemic Y. pestis challenge, and that cytokine-mediated Th1-type cellular immunity is very important to overcome the immunosuppression induced by Y. pestis infection. 7,31,48,49 In this study, we observed that the Y. pestis 201 or the EV induced not only the increase of IFN-γ and TNF-α production but also that of IL-2 secretion, revealing that the Y. pestis 201 or the EV could induce cytokine-mediated Th1-type cellular immune response in Chinese-origin rhesus macaque model. Moreover, the secretion of IL-4, IL-5, or IL-6 was significantly elevated in the immunized groups after immunization with the Y. pestis 201 or the EV.…”
Section: 84142mentioning
confidence: 77%
“…20 In addition, subunit vaccines based on F1 and LcrV antigens failed to fully protect African green monkeys, and the adequate evidence about whether or not they will protect humans has yet to be demonstrated. 21,22 Our previous study 23 and several reports 7,24,25 have indicated that subunit vaccines in alhydrogel elicit robust humoral immunity, and their potential to prime effective cellular immunity has yet to be demonstrated. Several studies suggest that antibodies alone may not provide optimal protection against plague, and that vaccines harnessing both humoral and cellular defense mechanisms should provide superior defense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the Trudeau Institute showed that IFN-, TNF-, and nitric oxide synthase 2, key elements of cellular immunity, provided critical protective functions during humoral defense against lethal pulmonary Y. pestis infection. Vaccination with live Y. pestis (KIM5 pCD1 + , pMT + , pPCP + , pgm -) primes CD4 and CD8 T cells that in synergy protect against mortal pulmonary Y. pestis infection [71].…”
Section: Cellular Immune Responses To Y Pestismentioning
confidence: 99%
“…This does not exclude the possibility that stimulation of cell-mediated immunity also may contribute to long-term resistance to plague. A recent study by Parent et al (2005) demonstrated protection against pneumonic disease in B cell-deficient mice (mMT mice) via adoptive transfer of Y. pestis-primed T cells. Focus on this aspect of the host response to plague is a new emergence and remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%